Improvement of the cell performance in the ZnS/Cu(In, Ga)Se2 solar cells by the sputter deposition of a bilayer ZnO : Al film. (6th December 2012) - Shin, Dong Hyeop; Kim, Ji Hye; Shin, Young Min; Yoon, Kyung Hoon; Al‐Ammar, Essam A.; Ahn, Byung Tae
ABSTRACT ZnS is a candidate to replace CdS as the buffer layer in Cu(In, Ga)Se2 (CIGS) solar cells for Cd‐free commercial product. However, the resistance of ZnS is too large, and the photoconductivity is too small. Therefore, the thickness of the ZnS should be as thin as possible. However, a CIGS solar cell with a very thin ZnS buffer layer is vulnerable to the sputtering power of the ZnO : Al window layer deposition because of plasma damage. To improve the efficiency of CIGS solar cells with a chemical‐bath‐deposited ZnS buffer layer, the effect of the plasma damage by the sputter deposition of the ZnO : Al window layer should be understood. We have found that the efficiency of a CIGS solar cell consistently decreases with an increase in the sputtering power for the ZnO : Al window layer deposition onto the ZnS buffer layer because of plasma damage. To protect the ZnS/CIGS interface, a bilayer ZnO : Al film was developed. It consists of a 50‐nm‐thick ZnO : Al plasma protection layer deposited at a sputtering power of 50 W and a 100‐nm‐thick ZnO : Al conducting layer deposited at a sputtering power of 200 W. The introduction of a 50‐nm‐thick ZnO : Al layer deposited at 50 W prevented plasma damage by sputtering, resulting in a high open‐circuit voltage, a large fill factor, and shunt resistance. The ZnS/CIGS solar cell with the bilayer ZnO : Al film yielded a cell efficiency of 14.68%. Therefore, the application of bilayer ZnO : Al film to the window layer is suitable for CIGS solar cells with a ZnS buffer layer. Copyright © 2012 John Wiley & Sons, Ltd.